Problems encountered by students in learning the theme of racism in Richard Wright’s Black boy - Chizuome Victor Obidiebube; Echezona Ifejirika (Humanities Horizon, 2026)
Racism is one of the themes explored in literary arts. Systematic investigations into the teaching of the theme of racism in English novels in senior secondary schools in Anambra State have been scarce. The aim of this study therefore is to investigate the teaching of the theme of racism in English novels in senior secondary schools in Ihiala Local Government Area of Anambra State. The objective of the study wass to identify the problems encountered by students in learning the theme of racism in Black Boy in senior secondary schools and to identify possible remedies to the constraints for effective teaching and learning of the theme of racism in Black Boy in senior secondary schools. The study adopts a descriptive survey design. Purposive sampling technique was used to select Richard Wright's Black Boy for the study. The instrument used for data collection was the questionnaire. The theoretical framework adopted for this study was McClelland theory of achievement and motivation. The study reveals that the unfamiliar background of the author constitutes a problem for 90% of the respondents, thereby making it difficult for both students and teachers to determine the setting, theme, and other things about the novel. The study concludes that the learners need proper understanding of the theme of racism to adjust properly in their environment. The paper recommends that the government should employ more English teachers, especially at the senior secondary level.